2009
DOI: 10.1158/0008-5472.can-08-3467
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the SMRT/NCoR2 Corepressor Correlates with JAG2 Overexpression in Multiple Myeloma

Abstract: Multiple myeloma (MM) is a clonal B-cell neoplasm that accounts for 10% of all malignant hematologic neoplasms and that affects terminally differentiated B cells (i.e., plasma cells). It is now well recognized that the cytokine interleukin-6 (IL-6) is a major cytokine that promotes the proliferation of malignant plasma cells in MM. The IL-6 gene can be regulated by the NOTCH genes products. We have previously shown that the NOTCH ligand, JAG2, is overexpressed in MM. To investigate the mechanism(s) leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 37 publications
3
69
0
Order By: Relevance
“…Overexpression of Jagged2 can be triggered either by promoter hypomethylation, 12 through aberrant expression of the ubiquitin ligase Skeletrophin 13 or by loss of SMRT/NCoR2 corepressor, which results in abnormal acetylation of the Jagged2 promoter. 14 In MM, Notch confers resistance to apoptotic stimuli and protects against chemotherapy-induced toxicity. 15, 16 Nefedova et al 15 described that Notch signalling is involved in de novo drug resistance triggered by bone marrow stroma.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Jagged2 can be triggered either by promoter hypomethylation, 12 through aberrant expression of the ubiquitin ligase Skeletrophin 13 or by loss of SMRT/NCoR2 corepressor, which results in abnormal acetylation of the Jagged2 promoter. 14 In MM, Notch confers resistance to apoptotic stimuli and protects against chemotherapy-induced toxicity. 15, 16 Nefedova et al 15 described that Notch signalling is involved in de novo drug resistance triggered by bone marrow stroma.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that downregulating cyclin D1 by SC-203048 or PTL may be a factor contributing to the tumor growth inhibition. SMRT is one of the most common transcriptional repression factors and plays an important role in several cancers [27][28][29]. Our previous study showed that decreased expression of SMRT existed in THP-1 cell line, and it is an important downstream molecule of FLT3/p65 signaling pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described [27]. Briefly, protein lysates were prepared by incubating cells with a lysis buffer as described [27].…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, protein lysates were prepared by incubating cells with a lysis buffer as described [27]. Cell debris was removed by centrifugation (14,000×g, 15 min at 4°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation